Cover Image: Volume 20, Issue 6. Issue 6 (4th November 2018) - Lukas, Paul; Olsson, Lennart
Abstract : The cover image is based on the Research Bapx1 is required for jaw joint development in amphibians, by Paul Lukas and Lennart Olsson, https://doi.org/10.1111/ede.12267 .